2015
DOI: 10.2131/jts.40.667
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skin phototoxicity study using SD rats by transdermal and oral administration

Abstract: -Guinea pigs are the most frequently used animals in phototoxicity studies. However, general toxicity studies most often use Sprague-Dawley (SD) rats. To reduce the number of animals needed for drug development, we examined whether skin phototoxicity studies could be performed using SD rats. A total of 19 drugs that had previously been shown to have phototoxic potential and 3 known phototoxic compounds were administered transdermally to guinea pigs and SD rats. Eleven of the potentially phototoxic drugs and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Therefore, the drug should have distributed in the skin sufficiently before anesthesia occurred. Moreover, in a previous report (Yonezawa et al, 2015), we showed that the phototoxicity of multiple drugs can be detected under the same anesthesia conditions. Thus, it was confirmed that pentobarbital anesthesia did not affect the phototoxicity evaluation.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Therefore, the drug should have distributed in the skin sufficiently before anesthesia occurred. Moreover, in a previous report (Yonezawa et al, 2015), we showed that the phototoxicity of multiple drugs can be detected under the same anesthesia conditions. Thus, it was confirmed that pentobarbital anesthesia did not affect the phototoxicity evaluation.…”
Section: Discussionmentioning
confidence: 60%
“…However, further studies are needed in order to confirm that this toxicity evaluation method can also be used to evaluate drugs with accumulative properties, like meloxicam (Seto et al, 2013;Türck et al, 1997), or that are degraded by metabolic enzymes, like amiodarones (Allen, 1993;Elsherbiny et al, 2008;Yonezawa et al, 2015). These drugs may affect the TK parameters throughout the dosing period, and may cause different phototoxic reactions between the first administration and final administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations